Comment remotiver un cliché historiographique ? Poésie du xviiie siècle et baroque des anthologies - Cartron, Maxime (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2021)
Today, eighteenth-century poetry is undervalued by readers and scholars alike, still the victim of a persistent bias among French literary historians who consider this period as rationalist and antipoetic, an era of unfortunate verse that was fortunately ushered out by Romanticism. By reading a corpus of anthologies of seventeenth-century French poetry published in the twentieth century, this article investigates a particular modality of this invalidation: how the aesthetic merits of the Baroque are elaborated against highly critical readings of eighteenth-century poetry. “Baroquist” anthologists deliberately (mis)read Enlightenment-era poetry as insipid in order to value and define “their” object of study more forcefully. Should we believe these critics, the Baroque and the Enlightenment periods would seem to be wholly antithetical to each other: the former rife with orphic creative flare, celebrated as the cradle of modern poetry, and the latter suffering from a total lack of poetic artistry. The aim of this article is to show the ways in which Baroquist anthologies see eighteenth-century poetry as “post-classic” at best, and to offer a rationale for their damaging historiographical strategy.